1990
DOI: 10.1016/0304-3959(90)92824-a
|View full text |Cite
|
Sign up to set email alerts
|

Types and causes of pain in cancer of the head and neck

Abstract: In a series of 25 patients with head dnd neck cancer who had severe pain, the type and cause of the pain were analyzed. There were two types of pain: nociceptive and nonnociceptive. Nineteen (76%) patients had nociceptive pain that could be subdivided into actual nociceptive pain (9 patients), nociceptive nerve pain (8 patients), or referred pain (2 patients). The cause of nociceptive pain was secondary to tumor recurrence in 16 patients and secondary to benign inflammation in 3 patients. Of the six (23%) case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
37
2
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 2 publications
6
37
2
1
Order By: Relevance
“…The rich blood supply and large numbers of nerves in the head and neck may affect tumor growth and/or pain. 23,24 Peripheral nociceptive mechanisms consistent with mechanical allodynia and hypersensitivity have been reported responsible for producing pain in patients with oral cancer. 25 For example, metabolic products of arachidonic acid, such as prostaglandins, are produced by OSCC cells, which sensitize primary afferent nociceptors and produce hyperalgesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rich blood supply and large numbers of nerves in the head and neck may affect tumor growth and/or pain. 23,24 Peripheral nociceptive mechanisms consistent with mechanical allodynia and hypersensitivity have been reported responsible for producing pain in patients with oral cancer. 25 For example, metabolic products of arachidonic acid, such as prostaglandins, are produced by OSCC cells, which sensitize primary afferent nociceptors and produce hyperalgesia.…”
Section: Discussionmentioning
confidence: 99%
“…25 This type of pain is histologically associated with tumor infiltration and compression of peripheral nerves and nociceptive receptors. 24 Highly invasive tumors may directly stimulate peripheral nerve endings and nociceptive receptors. Since we previously reported that tumor size was not correlated with pain, 15 oral cancer pain likely does not result from the mass effect of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,8,9 Because pain may be the first symptom of recurrent disease, we have retrospectively analyzed the importance of pain assessment and the diagnosis of tumor recurrence with special reference to referred pain.…”
mentioning
confidence: 99%
“…Neuropathic pain is pain associated with injury or disease of the peripheral or central nervous systems, which may result in pathophysiological changes such as ectopic (spontaneous or evoked) discharge by nerves, microneuroanatomical changes, central sensitization, and many others beyond the scope of this review (Macintyre & Schug, 2007). Neuropathic pain for patients with head and neck cancer may involve all sensory nerves in the face, skull, neck and shoulders (Vecht et al, 1992). Some common symptoms of neuropathic pain experienced by the patients include spontaneous continuous burning (81%), shooting pain (69%) and allodynia (88%) -which describes abnormal pain elicited by light touch (Sist et al, 1999;Merskey & Bogduk, 1994).…”
Section: Aetiology Of Painmentioning
confidence: 99%